2020
DOI: 10.1063/5.0024200
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of the aerosol behavior in intra-acinar region of a human lung

Abstract: The determination of the particle dynamics in the human acinar airways having millions of alveoli is critical in preventing potential health problems and delivering therapeutic particles effectively to target locations. Despite its complex geometrical structure and complicate wall movements, the advanced calculation simulations can provide valuable results to accurately predict the aerosol deposition in this region. The objective of this study was to numerically investigate the aerosol particle transport and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…The models presenting the human pulmonary acinus are validated with the numerical results of Darquenne et al [28] and Ciloglu et al [43], and, applied for three breathing conditions with mouth flow rates 15 (light), 30 (normal), and 60 (heavy) LPM for an average human adult with tidal volume 500 mL, FRC of 3 L and total lung capacity 6 L. During one breathing cycle, equal inspiration and expiration times are assumed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The models presenting the human pulmonary acinus are validated with the numerical results of Darquenne et al [28] and Ciloglu et al [43], and, applied for three breathing conditions with mouth flow rates 15 (light), 30 (normal), and 60 (heavy) LPM for an average human adult with tidal volume 500 mL, FRC of 3 L and total lung capacity 6 L. During one breathing cycle, equal inspiration and expiration times are assumed.…”
Section: Resultsmentioning
confidence: 99%
“…The pulmonary region of the lung consists of the respiratory bronchioles (with partly surrounding alveoli), the alveolar ducts (completely covered by alveoli), and the alveolar sacs (the blind-ending terminations of alveolar ducts) [42]. To represent the airflow in these generations, i.e., generation 17 (G17), 18 (G18), and 23 (G23), idealized models developed in the author's previous study [43] have been employed, as shown in figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Madas et al (2020) employed a lung model based on a stochastic deposition, which was developed by Koblinger and Hofmann (1990) to find out the deposition of viral loads and revealed that over 60% of the inhaled viral masses were deposited in the extrathoracalis (upper), which are the portion of the human lung airways, and suggested to affect the upper airways and if not diagnosed, could eventually develop into pneumonia. Other researchers focused on aerosol behavior in the intra-distal region of a simplistic lung model in the presence of different breathing conditions ( Ciloglu, 2020 ), gravity and surface tension effects on micro-bubbles in simplistic bifurcated airways ( Munir and Xu, 2020 ), mask-wearing effects in upper respiratory geometry ( Xi et al , 2020 ), aerosol transport in phantom lung bronchioles ( Mallik et al , 2020 ), cough exhalation from a 18-generation simplistic airways ( Si et al , 2021 ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…This event is analogous to the breakup of liquid thread that breaks up due to P–R instability. In parallel, other respiratory events such as coughing and sneezing are the spasmodic and complex event [3] , [22] , [26] , [27] that triggers the involuntary discharge of fluid from the lungs [1] , [33] . A cough is a spontaneous and persistent reflex that effectively clears the large breathing passages of fluids and other foreign particles.…”
mentioning
confidence: 99%